A pilot study: does oxygenated water support lactate clearance kinetics after simulated games in elite taekwondo athletes? - Chung, Y.-K.; Wu, Y.-N.; Wang, S.-C.; He, C.-S. (Journal of Exercise and Nutrition, 2024)
Introduction: To further understand the effects of ingesting oxygenated water supplementation (OS) on heart rate (HR), rating of perceived exertion (RPE), and blood lactate (BL) during two simulated combats in elite Taekwondo athletes.